Security Analysis of the Graphical Password-Based Authentication Systems with Different Attack Proofs - Golar, Priti C.; Sharma, Rika (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Graphical password authentication is an effective alternative to the textual based password as the text based passwords are difficult to be remembered. One of the disadvantage is that there are several attacks existing in these schemes that disrupts the integrity of the websites. In this paper, a detailed security analysis for various kinds of attacks existing in a graphical password authentication system is presented. Initially, the scenario of graphical authentication system along with its types are narrated. Then, the major security threats encountered in the graphical password authentication systems till date are explored. Based on the security threats arising in the authentication systems, the zero knowledge attack proof is formulated and the analysis is explained. More importance is given to the shoulder surfing attack and the proof is explained with the help of an application scenario. The introduced application scenario includes a 3D graphical password authentication system for website login. The scenario is proved to be shoulder surfing resistance using the zero knowledge proof protocol. With the analysis, it is proved that the graphical passwords are highly significant in maintaining the integrity of the websites.